Curcumin analog B14 has high bioavailability and enhances the effect of anti‐breast cancer cells in vitro and in vivo. Issue 2 (31st December 2020) - Shen, Hui; Shen, Jianfen; Pan, Huan; Xu, Longsheng; Sheng, Han; Liu, Beibei; Yao, Ming
Abstract: Curcumin has a variety of anticancer properties, but low bioavailability prevents its use in chemotherapeutic applications. To address this problem, we tested the efficacy of the synthetic curcumin analog B14 in breast cancer cells and explored the mechanism by which B14 inhibits proliferation and metastasis of breast cancer cells. We used the breast cancer cell line MCF‐7, MDA‐MB‐231 to study the anticancer effects of B14 and assessed cell viability, cell migration and invasion, cell cycle, and apoptosis, in addition, the antitumor effect of B14 in vivo was examined in mice bearing MDA‐MB‐231 cells. We found that, as the concentration of B14 increased, cell viability decreased in a dose‐dependent manner. Compound B14 exerted the best antitumor activity and selectivity for MCF‐7 and MDA‐M‐231 cells (IC50  = 8.84 μmol/L and 8.33 μmol/L, respectively), while its IC50 value for MCF‐10A breast epithelial cells was 34.96 μmol/L. B14 has been shown to be a multi‐targeted drug that alters the expression of cyclin D1, cyclin E1, and cyclin‐dependent kinase 2 (CDK2), and ultimately induces G1 phase cell cycle arrest. At the same time, B14 activates the mitochondrial apoptosis pathway in breast cancer cells. Furthermore, B14 was more effective than curcumin in inhibiting cell migration, invasion, and colony formation. In tumor‐bearing mice, analog B14 significantly reduced tumor growth and inhibited cell proliferation and angiogenesis. The pharmacokinetic test found that B14 was more stable than curcumin in vivo. Our data reveal the therapeutic potential of the curcumin analog B14 and the underlying mechanisms to fight breast cancer cells. Abstract : The results of in vitro and in vivo studies indicate that B14 has better bioavailability compared with curcumin and can exert antitumor effects on breast cancer through mitochondrial apoptotic pathway and cell cycle G1 arrest. The study of curcumin analog B14 multitargeting antitumor mechanism may provide a new strategy for the design and development of anticancer drugs based on curcumin.